Analisis Sistem Kompensasi UKM XYZ dengan Metode Adhered dan Overlapping - Khansa Aristya Pramesti; Shofi Kirana Aryati; Alysha Dzahabiyya Aurora Riyadi; Shafa Nabila; Diah Pitaloka Saraswati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Every company has the responsibility to provide salaries to employees in accordance with applicable regulations. Providing wages according to standards aims to ensure that workers can earn sufficient income to meet the needs of a decent living. The compensation system is considered crucial in a company because it has a direct influence on employee motivation and performance. This research aims to analyze the compensation system in UKM XYZ, a company in the food and beverage industry. The data analysis method used is the salary mapping analysis method which includes the Adhered method and the Overlapping method. The research results show that the actual basic salary in UKM for several job titles is still below the West Java UMP. Based on the results of the comparative analysis of salary mapping according to the adhered and overlapping methods, it was found that the overlapping method is a salary mapping that is in accordance with the financial capabilities of UKM because it does not make much difference to the total salary available and the ability of UKM to afford this amount.